Features of teaching technical, physical and mathematical disciplines by means of distance learning in guarantine conditions - Sadkovyi , V.; Mietielov О.; Tarasenko , O.; Goroneskul , M. (New Collegium, 2020)
The article deals with the actual problem of introduction of distance learning during lockdown. Quarantine measures in educational institutions made it impossible for traditional forms of education and direct contact of lecturers with students at the classroom. Acceptance of this fact indicated the distance learning is the only way of in the current circumstances, and forced skeptics to change their views and beliefs about distance learning and to take possession of its technologies. The authors carried out a careful analysis of the legal documents that became the basis for the introduction of distance learning in educational institutions of Ukraine, in particular at universities. World education and science trends in distance learning are explored and other countries’ experiences of using technological innovations in educational services was examined. The review of the psycho-pedagogical literature on the organization of distance learning helped to distinguish such basic features: interactivity; using of new achievements of information technologies in the educational process; business communication skills during video communications, and during group video conferencing. The conducted survey of students showed that the advantages of distance learning are: the lack of a rigid time frame for mastering the learning material; the opportunity to independently organize your time intended for training; access to training materials and educational services at any time; the use of modern means of communication with teachers; the opportunity to get advice at a convenient time, quickly get an answer to questions through chat services of instant messengers or video communication technology; lack of transportation and accommodation costs and etc. The article provides examples of use by teachers of the National University of Civil Defence of Ukraine of such web resources as Zoom, Skype and etc. for educational online lectures, online practical classes, and technology of 3D-virtual tours to production enterprises during quarantine.